Implant and Midterm Outcomes of the Subcutaneous Implantable Cardioverter-Defibrillator Registry: The EFFORTLESS Study - Boersma, Lucas; Barr, Craig; Knops, Reinoud; Theuns, Dominic; Eckardt, Lars; Neuzil, Petr; Scholten, Marcoen; Hood, Margaret; Kuschyk, Juergen; Jones, Paul; Duffy, Elizabeth; Husby, Michael; et al. (Journal of the American College of Cardiology, 2017)
BACKGROUND: The subcutaneous implantable cardioverter-defibrillator (S-ICD) was developed to defibrillate ventricular arrhythmias, avoiding drawbacks of transvenous leads. The global EFFORTLESS S-ICD (Evaluation oF FactORs ImpacTing CLinical Outcome and Cost EffectiveneSS of the S-ICD) registry is collecting outcomes in 985 patients during a 5-year follow-up. OBJECTIVES: The primary goal of the EFFORTLESS registry is to determine the safety of the S-ICD by evaluating complications and inappropriate shock rate. METHODS: This is the first report on the full patient cohort and study endpoints with follow-up ≥1 year. The predefined endpoints are 30- and 360-day complications, and shocks for atrial fibrillation or supraventricular tachycardia. RESULTS: Patients were followed for 3.1 ± 1.5 years and 82 completed the study protocol 5-year visit. Average age was 48 years, 28% were women, ejection fraction was 43 ± 18%, and 65% had a primary prevention indication. The S-ICD system and procedure complication rate was 4.1% at 30 days and 8.4% at 360 days. The 1-year complication rate trended toward improvement from the first to last quartile of enrollment (11.3% [quartile 1]) to 7.8% [quartile 2], 6.6% [quartile 3], and 7.4% [quartile 4]; quartile 1 vs. quartiles 2 to 4; p = 0.06). Few device extractions occurred due to need for antitachycardia (n = 5), or biventricular (n = 4) or bradycardia pacing (n = 1). Inappropriate shocks occurred in 8.1% at 1 year and 11.7% after 3.1 years. At implant, 99.5% of patients had a successful conversion of induced ventricular tachycardia or ventricular fibrillation. The 1- and 5-year rates of appropriate shock were 5.8% and 13.5%, respectively. Conversion success for discrete spontaneous episodes was 97.4% overall. CONCLUSIONS: This registry demonstrates that the S-ICD fulfills predefined endpoints for safety and efficacy. Midterm performance rates on complications, inappropriate shocks, and conversion efficacy were comparable to rates observed in transvenous implantable cardioverter-defibrillator studies. (Evaluation oF Factors ImpacTing CLinical Outcome and Cost EffectiveneSS of the S-ICD [The EFFORTLESS S-ICD Registry]; NCT01085435).
Keywords: výsledek terapie; primary prevention; secondary prevention; Male; Tachycardia, Ventricular; následné studie; leadless; mužské pohlaví; inappropriate therapy; registrace; Defibrillators, Implantable; Follow-Up Studies; Treatment Outcome; Time Factors; lidé; ženské pohlaví; Humans; defibrilátory implantabilní; časové faktory; Registries; ventricular arrhythmias; appropriate therapy; Female; lidé středního věku; komorová tachykardie; Middle Aged